2012
DOI: 10.4103/0255-0857.93040
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of healthcare-associated infections in general practice: Current practice and drivers for change in a French study

Abstract: Our results show that there are significant differences between current practice and laid-down professional guidelines. Policies for improvement of hygiene must take into account barriers and motivating factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…Other studies have shown the need to deepen the awareness of primary care professionals in order to possess knowledge and to adopt evidence-based practices and standard operating procedures or practice guidelines [ 23 , 24 ]. In this sense, we believe that the results of the study may be useful for those systems with a decentralised primary care network in their hospital system.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown the need to deepen the awareness of primary care professionals in order to possess knowledge and to adopt evidence-based practices and standard operating procedures or practice guidelines [ 23 , 24 ]. In this sense, we believe that the results of the study may be useful for those systems with a decentralised primary care network in their hospital system.…”
Section: Discussionmentioning
confidence: 99%
“…On top of that, outbreaks result in significant cost to health organizations, high cost of modifications, and lack of time/space. 4,5 One of the most persistent issues is the rapid depletion of personal protective equipment (PPE).…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Although several studies have evaluated IPC practices and structures in hospitals and long-term care facilities, studies focusing on outpatient care are less common. [10][11][12] Good IPC practices are effective at reducing rates of infection in all health care settings, including primary care. 13 The medical implications of a failure to implement IPC procedures have been shown to be serious in, for example, hospitals, whereas they seem nonexistent in primary care settings.…”
mentioning
confidence: 99%